Transurethral resection, neoadjuvant chemotherapy and accelerated hyperfractionated radiotherapy – concomitant boost, with or without concurrent cisplatin, for patients with invasive bladder cancer – clinical outcome - Nowak-Sadzikowska, Jadwiga; Jakubowicz, Jerzy; Skóra, Tomasz; Pudełek, Katarzyna (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study : To evaluate the toxicity, clinical effectiveness and survival rate of transurethral resection, neoadjuvant chemotherapy and accelerated hyperfractionated radiotherapy (concomitant boost), with or without concurrent cisplatin in patients with muscle invasive bladder cancer. Material and methods: Between March 2004 and December 2009, 35 patients with histologically proven invasive carcinoma of the bladder (T2-4a, N0-1, M0), who were fit for combined radiochemotherapy and refused radical surgery or were medically or surgically inoperable, were selected for the bladder-sparing protocol. Results: In this study, twenty-five patients (25/35; 72%) received two cycles of neoadjuvant chemotherapy, and ten of them (10/35; 28%) only one, because of treatment-related toxicity. In twenty-one patients (21/35; 60%) chemotherapy consisting of gemcitabine with cisplatin and in fourteen patients (14/35; 40%) gemcitabine with carboplatin were applied. Only 13 patients (13/35; 37%) received combined irradiation with cisplatin. All patients completed their planned course of radiation therapy. Complete response (CR) occurred in 26/35 (74%) patients, partial response (PR) in 2/35(6%), and stable disease (SD) in 7/35 (20%). The overall actuarial survival rates at 3 and 5 years were 75% and 66%, respectively. Disease-specific actuarial survival rates at 3 and 5 years were 81% and 71%, respectively. Conclusions : Conservative treatment of patients with muscle-invasive bladder cancer by transurethral resection, neoadjuvant chemotherapy, and accelerated hyperfractionated radiotherapy with concomitant boost, with or without concurrent cisplatin, provides a high probability of local and distal response with acceptable toxicity in properly selected patients.